Epidemiological study of animal bite cases attending a tertiary care hospital in Tripura: North-East India - Acharjee, Manish; Saha , Goutam (International Journal Of Community Medicine And Public Health, 2023)
Background: This research article presents an epidemiological study in Tripura, North-east India, investigating animal bite cases at a tertiary care hospital. Animal bites pose significant public health concerns, including potential zoonotic disease transmission. The study aims to assess animal bite incidence, envenoming, and treatment-seeking behaviours among victims. Data from individuals over one year old will reveal the burden of animal bites on healthcare facilities, guiding effective prevention and management strategies for this pressing health issue. Methods: A cross-sectional study at AGMC and GBP Hospital, Tripura, assessed animal bite patterns referred to the ARV centre (2018–2021). Included animal-related bites and excluded incomplete data. Collected age, gender, socio-economic status, biting animal, and bite category. Staff ensured nationwide surveillance. Categorised subjects by age. Results: The cross-sectional study investigated animal bite patterns at AGMC and GBP Hospital, Agartala, Tripura, from 2018 to 2021. Analysis revealed male adults (20-39 years, 41.7%) were most affected, predominantly by dogs (57.58%). The APL category showed the highest frequency (70.79%). Missing category bites decreased, while third category bites increased over time. The winter months had higher frequencies of animal bites. Continued surveillance and targeted interventions are vital for effective prevention. Conclusions: This study highlights male adults (20–39 years old) as being most affected, predominantly by dog bites. The APL category showed higher susceptibility. Continued surveillance and targeted interventions are crucial for effective prevention.